2008
DOI: 10.1007/s11748-007-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular hemangioma in the right ventricle

Abstract: Intramuscular cardiac hemangiomas are extremely rare. We describe a 74-year-old man with a tumor occupying the apex of the right ventricle that was incidentally diagnosed by echocardiography. Computed tomography and coronary angiography showed that the tumor arose from the ventricular septum and that the feeding artery was a branch of the right coronary artery. The tumor was completely excised, and the postoperative course was uneventful. Histological examination revealed that the tumor was a cardiac hemangiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…The incidence of cardiac hemangioma is very low, accounting for 5% to 10% of all benign cardiac tumors 2 . Histologically, cardiac hemangioma can be classified as cavernous hemangioma, capillary hemangioma, intermuscular hemangioma and hemangioendothelioma, of which cavernous hemangioma is the most common 1 . Intermuscular hemangioma occurs more frequently in skeletal muscles of the extremities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of cardiac hemangioma is very low, accounting for 5% to 10% of all benign cardiac tumors 2 . Histologically, cardiac hemangioma can be classified as cavernous hemangioma, capillary hemangioma, intermuscular hemangioma and hemangioendothelioma, of which cavernous hemangioma is the most common 1 . Intermuscular hemangioma occurs more frequently in skeletal muscles of the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Intermuscular hemangioma in the heart is very rare and, to our knowledge, only three cases have been reported in the world literature. In 2008, Sotoda et al 1 reported a case of intermuscular hemangioma in the right ventricle, which was resected completely. In 1991, Oda et al 3 reported a case of intermuscular hemangioma, which also occurred in the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, most cardiac vascular anomalies are termed “(hem)angiomas” and are classified according to the main type of vessel involved or their topographic localization within the heart (endocardial, intramuscular, or epicardial) [9, 10]. However, the general approach to classify all benign vascular cardiac tumours as (hem)angioma needs further specification.…”
Section: Discussionmentioning
confidence: 99%